Aspek Perubahan Sosial dan Mindset tentang Sanitasi - Caesar, Yureta Wahyu; Ayuningtiyas, Kartika; Agustina, Tri Siwi (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2022)
Community involvement and the provision of material assistance as well as socialization in the activities of providing clean water and sanitation are the main objectives in this study. In this study the authors conducted a method with a preliminary survey and research data collection used were observation, interviews and documentation techniques. In this study, the Yayasan Senyum Desa plays a role as a non-governmental organization which can provide change in the Tengger village community. This study describes the role and involvement of the community and non-governmental organizations in participating in counseling for water sanitation processing and making nutritious food. This study also explains the facts behind community service which is material and socialization can provide social influence and mindset for the people of Tengger village.